Radiofrequency Catheter Ablation of Supraventricular Tachycardia in Patients With Pulmonary Hypertension: Feasibility and Long-Term Outcome - Zhou, Bin; Zhu, Yong-Jian; Zhai, Zheng-Qin; Weng, Si-Xian; Ma, Ya-Zhe; Yu, Feng-Yuan; Qi, Ying-Jie; Jiang, Yi-Zhou; Gao, Xin; Xu, Xi-Qi; Jiang, Xin; Jing, Zhi-Cheng; et al. (Frontiers in Physiology, 2021)
BACKGROUND: Supraventricular tachycardia (SVT) occurs commonly and is strongly correlated with clinical deterioration in patients with pulmonary hypertension (PH). This study aimed to investigate the feasibility and long-term outcome of radiofrequency catheter ablation (RFCA) in PH patients with SVT. METHODS: Consecutive PH patients with SVT who were scheduled to undergo electrophysiological study and RFCA between September 2010 and July 2019 were included. The acute results and long-term success of RFCA were assessed after the procedure. RESULTS: In total, 71 PH patients with 76 episodes of SVT were analyzed. Cavotricuspid isthmus-dependent atrial flutter (n = 33, 43.5%) was the most common SVT type, followed by atrioventricular nodal reentrant tachycardia (n = 16, 21.1%). Of the 71 patients, 60 (84.5%) underwent successful electrophysiological study and were subsequently treated by RFCA. Among them, acute sinus rhythm was restored in 54 (90.0%) patients, and procedure-related complications were observed in 4 (6.7%) patients. Univariate logistic regression analysis showed that cavotricuspid isthmus-independent atrial flutter (odds ratio [OR] 25.00, 95% confidence interval [CI] 3.45-180.98), p = 0.001) and wider pulmonary artery diameter (OR 1.19, 95% CI 1.03-1.38; p = 0.016) were associated with RFCA failure. During a median follow-up of 36 (range, 3-108) months, 7 patients with atrial flutter experienced recurrence, yielding a 78.3% 3-year success rate for RFCA treatment. CONCLUSION: The findings suggest that RFCA of SVT in PH patients is feasible and has a good long-term success rate. Cavotricuspid isthmus-independent atrial flutter and a wider PAD could increase the risk for ablation failure.